Synchronization of Treadmill Speed to Bicycle Model Speed Based on PID Controller - Baskoro Latu Anurogo (Politeknik Negeri Lhokseumawe, 2022)
Bad weather and crowded vehicle lanes are often obstacles for cyclists during practice. Bicycle treadmills are the right solution to answer these demands. A person can cycle on a treadmill without having to leave the room. The rotation speed of the treadmill will be determined by the rotational speed of the bicycle wheels, so the bicycle will not fall off the treadmill. For this reason, this study aims to design a PID-based controller that will control the rotational speed of the treadmill so that it is in sync with the rotational speed of the bicycle wheel. The rotation of the bicycle wheel is represented by the wheel of a bicycle model that rotates on a treadmill, while the treadmill is represented by a model in the form of a conveyor. The results showed that in the first second, the conveyor speed was not the same as the speed of the bicycle model. Even so, after 1.5 seconds, the conveyor can catch up to the speed of the bike model. Despite some glitches, the conveyor can keep up with the speed of the bike model.